Autologous Temporalis Subfascial Fat Graft for Skull Base Repair: A Novel Technique. Issue 4 (19th January 2021) - Lee, Paul; Krisht, Khaled M; Cai, Li; Krisht, Ali F
Abstract: BACKGROUND: Autologous abdominal fat grafts are occasionally used in the repair of skull base exposures. This surgical procedure typically requires an additional surgical site and may have unexpected postoperative complications. OBJECTIVE: To describe an operative technique for harvesting subfascial fat from the temporal extension of the buccal fat pad for the repair of skull base defects. METHODS: We review the pertinent anatomy of the temporalis subfascial fat pad and discuss the technique used to harvest the subfascial fat component in a clinical presentation. RESULTS: A pretemporal approach was performed for clip ligation of an anterior circulation aneurysm. A standard frontotemporal incision was made with an interfascial flap to preserve the frontalis branches of the facial nerve. The subfascial fat was inspected and determined to be adequate for harvesting. Monopolar cauterization was carefully utilized to remove the fat. During closure, the graft was used to repair a pneumatized clinoid sinus and for the dural repair of the pretemporal exposure. The patient did not have any postoperative complications. CONCLUSION: Autologous temporalis subfascial fat graft is a viable and safe technique for skull base dural and sinus repair during frontotemporal approaches in select patients. This technique avoids an additional surgical procedure and potential complications that may be associated with it.